2014
DOI: 10.1080/1750984x.2014.932423
|View full text |Cite
|
Sign up to set email alerts
|

Teamwork in sport: a theoretical and integrative review

Abstract: A commonly held belief in sports is the need for team members to be able to work well together in order for that team to be successful. Despite this assumption, research in the field of sport psychology has yet to formally or sufficiently conceptualize what is meant by teamwork. In this theoretical and integrative review, we draw from the extant organizational psychology and team development literature to present a multidimensional conceptual framework of teamwork in sport. We provide a working definition of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
190
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(202 citation statements)
references
References 76 publications
(157 reference statements)
6
190
1
5
Order By: Relevance
“…While the preparation (i.e., behaviors occurring before team task performance such as setting goals and action plans), execution (i.e., intra-task behaviors such as communication and coordination), and reflection (i.e., behaviors occurring following task performance such as performance monitoring and problem solving) dimensions have each been theorized to be implicated in fostering team performance [2, 79], is particularly noteworthy that interventions targeting the interpersonal dynamics of a team (i.e., managing interpersonal conflict and the provision of social support between members) also displayed significant effects in relation to team performance. Specifically, efforts to enhance interpersonal processes have generally been theorized to be related to supporting team maintenance more so than supporting team performance [2, 79]. However, the results from the current review provide evidence that training teams with regard to social support and interpersonal conflict management processes may actually be a useful way to enhance team performance.…”
Section: Discussionmentioning
confidence: 99%
“…While the preparation (i.e., behaviors occurring before team task performance such as setting goals and action plans), execution (i.e., intra-task behaviors such as communication and coordination), and reflection (i.e., behaviors occurring following task performance such as performance monitoring and problem solving) dimensions have each been theorized to be implicated in fostering team performance [2, 79], is particularly noteworthy that interventions targeting the interpersonal dynamics of a team (i.e., managing interpersonal conflict and the provision of social support between members) also displayed significant effects in relation to team performance. Specifically, efforts to enhance interpersonal processes have generally been theorized to be related to supporting team maintenance more so than supporting team performance [2, 79]. However, the results from the current review provide evidence that training teams with regard to social support and interpersonal conflict management processes may actually be a useful way to enhance team performance.…”
Section: Discussionmentioning
confidence: 99%
“…This study illustrated how team resilience processes were essential for the development of excellence which resonates with other research in sport psychology that has identified the critical role of transformational leadership, team leadership, and team identity during challenging situations in elite sport[4,29,30]. Importantly, in both studies conducted by Morgan et al[7,8**], team resilience was portrayed as a dynamic, temporal process.Teams do not exist in static environments[31,32] and these findings suggest that team resilience development should occur in accordance with the stage of a team's existence and the specific stressors encountered in that context and at that time. In summary, sport psychology research has captured the contextual and temporal nature of team resilience in elite sport and suggests that leveraging a team's collective resources can enhance their ability to withstand stressors and ultimately perform at the highest level.Running head: TEAM RESILIENCE REVIEW 8 Applied Implications A number of practical suggestions arise from team resilience research.…”
mentioning
confidence: 99%
“…For example, Burke et al (2014) proposed that the normative expectations of the group as well as status issues (i.e., status congruency) could be particularly influential sources of emergent cohesion perceptions. Also, as noted previously, McEwan and Beauchamp's (2014) model of teamwork suggests that cohesion has reciprocal relationships with several team processes (e.g., regulatory activities related to preparation, execution, evaluation, and adjustment). Despite repeated encouragement for research to test reciprocality, little exploration has been conducted relative to the effect of these variables on cohesion and cohesion's effect on regulatory activities,…”
Section: Broadening the Theoretical Scope Of Cohesion Researchmentioning
confidence: 63%